Pragmatistische Gedanken für die Geographie. - Geiselhart, Klaus; Steiner, Christian (Berichte zur Deutschen Landeskunde, 2012)
Doing Geography is intrinsically linked to methodological and meta-theoretical questions of how to produce knowledge. Therefore, every geographic research project implies an epistemological component, which is basically and essentially linked to the concept of reality and truth of the respective scholar. Given the traditional empirical strength of German speaking Geography, the current paper aims at introducing an alternative epistemological perspective and discusses the potential of American pragmatist philosophy for doing Geography. American Pragmatism is relatively unknown in the German speaking geographical discourse. Therefore, the paper focuses on introducing into some of its key elements. Probably its most intriguing element is the pragmatist concept of truth. Pragmatists postulate that our truths are produced in everyday processes of inquiry. Therefore, truth can be conceptualized as an outcome of practice. It is context-specific, dynamic, and contingent. However, this non-fundamentalist, pluralist and relativist notion of truth surprisingly has severe normative implications, calling for a democratic society and an anti-dogmatic scientific debate, in which we should engage in a practical and meaningful discussion about viable and alternative explanations and interpretations of our lived-in-world.